Fractalkine Modulates Microglia Metabolism in Brain Ischemia - Lauro, Clotilde; Chece, Giuseppina; Monaco, Lucia; Antonangeli, Fabrizio; Peruzzi, Giovanna; Rinaldo, Serena; Paone, Alessio; Cutruzzolà, Francesca; Limatola, Cristina (Frontiers in Cellular Neuroscience, 2019)
In the CNS, the chemokine CX3CL1 (fractalkine) is expressed on neurons while its specific receptor CX3CR1 is expressed on microglia and macrophages. Microglia play an important role in health and disease through CX3CL1/CX3CR1 signaling, and in many neurodegenerative disorders, microglia dysregulation has been associated with neuro-inflammation. We have previously shown that CX3CL1 has neuroprotective effects against cerebral ischemia injury. Here, we investigated the involvement of CX3CL1 in the modulation of microglia phenotype and the underlying neuroprotective effect on ischemia injury. The expression profiles of anti- and pro-inflammatory genes showed that CX3CL1 markedly inhibited microglial activation both in vitro and in vivo after permanent middle cerebral artery occlusion (pMCAO), accompanied by an increase in the expression of anti-inflammatory genes. Moreover, CX3CL1 induces a metabolic switch in microglial cells with an increase in the expression of genes related to the oxidative pathway and a reduction in those related to glycolytic pathway, which is the metabolic state associated to the pro-inflammatory phenotype for energy production. The data reported in this paper suggest that CX3CL1 protects against cerebral ischemia modulating the activation state of microglia and its metabolism in order to restrain inflammation and organize a neuroprotective response against the ischemic insult.